Assessment Of Anthropogenic Impact On Forest Ecosystem: A Case Study Of Kumbhalgarh Wildlife Sanctuary, India - Bhanwar V. R. Singh; Anjan Sen; Ravi Mishra; Ritika Prasad (Geography, Environment, Sustainability, 2023)
In the era of the modern world, natural resources are continuously diminishing and simultaneously the human population is also increasing, which is alarming for the present and future world. Global biodiversity is playing a pivotal role in all ecosystem services, meanwhile, anthropogenic activities and encroachment are the main drivers for the widespread loss of local biodiversity. In India, Kumbhalgarh Wildlife Sanctuary is situated in the world’s oldest Aravali Mountain range. Near protected areas of this wildlife sanctuary have an entire concentration of rural populations, which are interdependence with this forest ecosystem. The key objective of the research study is to measure the anthropogenic impact on Kumbhalgarh Wildlife Sanctuary. It’s a micro-level study based on primary and secondary data through GIS mapping as well as Socio- Economic & Physical factors to inter-connect with forest habitats. Especially, core and periphery LULC have been obtained from the Multispectral images from ETM+ and OLI sensors of Landsat satellites. This study examines the spatial and temporal patterns of LULC change along the boundary of Kumbhalgarh from 2000 to 2020. The research also describes land use and land cover pattern, forest cover and vegetation index, and human encroachment, Eventually, the situation would be alarming for the local biodiversity and habitat due to the high pressure of anthropogenic activities and encroachment.